The Effect of Education Level and Tax Incentives on MSME Taxpayer Compliance (Case Study on MSME Owners in Central Village) - Mukharomah, Nurul Rizki; Dali, Rahmat Mulyana; Yudiana (Program Studi Akuntansi Universitas Ibn Khaldun Bogor, 2023)
Taxes are the main source of state revenue. However, the contribution of MSMEs to taxes is still quite low. This will reduce state revenues from taxes. The purpose of this study is to analyze the effect partially and simultaneously on the variable level of education and tax incentives on MSME taxpayer compliance. This study used a quantitative research method, with a population of 175 MSMEs in Tengah Village, the sampling technique used was convenience sampling using the slovin formula, in order to obtain a sample of 30 MSMEs. This study uses multiple linear regression analysis using the SPSS application as a data processing application. The results showed that the level of education had no significant effect on MSME taxpayer compliance. Tax incentives have a significant effect on MSME taxpayer compliance. And the level of education and tax incentives simultaneously influence MSME taxpayer compliance.